Identifikasi Potensi Ekonomi Kreatif Sebagai Pendukung Desa Wisata: Studi Kasus di Desa Gili Indah - Wahyu Hidayat; Muhammad Zaroqi Rabbani; Lalu Muhammad Diwa Asmarandana; Laila Husni; Ika Wijayanti (Student Research Journal, 2024)
This study aims to determine the potential of the creative economy to support the development of gili Indah Tourism Village, Lombok, West Nusa Tenggara.This study uses qualitative methods with a case study approach.The data collection process uses observation, interview,and documentation methods.Furthermore, the data is processed using data analysis techniques Milles and Huberman which includes data reduction,assessment, and conclusion or verification. The results of this study revealed that Gili Indah village has a promising creative economic potential, especially in the handicraft subsector such as crafts from coconut shells, wood, and accessories from local materials that are hereditary cultural heritage. Creative economic potential in Gili Indah village has a very important role in supporting the development of Sustainable Tourism Village. The creative economy plays a role in providing products and services that become tourist attractions, increasing income and welfare of the community, preserving local culture and wisdom, and creating new jobs for rural communities.